2014
DOI: 10.1007/s00213-014-3478-5
|View full text |Cite
|
Sign up to set email alerts
|

Chronic cannabidiol treatment improves social and object recognition in double transgenic APPswe/PS1∆E9 mice

Abstract: This is the first study to investigate the effect of chronic CBD treatment on cognition in an AD transgenic mouse model. Our findings suggest that CBD may have therapeutic potential for specific cognitive impairments associated with AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
120
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(141 citation statements)
references
References 70 publications
15
120
0
6
Order By: Relevance
“…Though this effect is most often attributed to the psychoactive properties of THC, to some it seems counterintuitive to treat a progressive cognitive disorder with the derivatives of a drug known to worsen cognitive impairment. On the other hand, CBD was recently shown to improve socialization and object recognition in transgenic AD mice [94]. This reinforces the concept that the therapeutic effects of cannabinoids, particularly those without significant psychoactive effects, should continue to be examined.…”
Section: Sleep Disorderssupporting
confidence: 53%
“…Though this effect is most often attributed to the psychoactive properties of THC, to some it seems counterintuitive to treat a progressive cognitive disorder with the derivatives of a drug known to worsen cognitive impairment. On the other hand, CBD was recently shown to improve socialization and object recognition in transgenic AD mice [94]. This reinforces the concept that the therapeutic effects of cannabinoids, particularly those without significant psychoactive effects, should continue to be examined.…”
Section: Sleep Disorderssupporting
confidence: 53%
“…The meaning of this finding is still unknown. Imipramine and CBD presented protective effects under of different animal models of neurodegenerative conditions, such as brain ischemia (Pazos et al, 2012;Schiavon et al, 2010;Schiavon et al, 2014), Alzheimer's disease (Cheng et al, 2014), Parkinson's disease (LastresBecker et al, 2005), and schizophrenia (Gomes et al, 2015). The proneurogenic activity of CBD observed in the SVZ, therefore, might be related to its reparative and/or neuroprotective effects.…”
Section: Discussionmentioning
confidence: 99%
“…Collaterally, we evaluated the therapeutic profile of the 9 -THC and CBD combination in WT littermates used as a model of aging. We chose the combination of these two natural cannabinoids because, although previous findings revealed that both 9 -THC and CBD given alone resulted in beneficial cognitive effects in A␤PP/PS1 mice [13,16,17], the combination of 9 -THC and CBD was more effective than either cannabinoid alone in these transgenic animals when administered at early stages [13].…”
Section: Discussionmentioning
confidence: 99%